2013
DOI: 10.1002/ange.201308986
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Gold Nanovesicles with an Ultrastrong Plasmonic Coupling Effect for Photoacoustic Imaging and Photothermal Therapy

Abstract: The hierarchical assembly of gold nanoparticles (GNPs) allows the localized surface plasmon resonance peaks to be engineered to the near‐infrared (NIR) region for enhanced photothermal therapy (PTT). Herein we report a novel theranostic platform based on biodegradable plasmonic gold nanovesicles for photoacoustic (PA) imaging and PTT. The disulfide bond at the terminus of a PEG‐b‐PCL block‐copolymer graft enables dense packing of GNPs during the assembly process and induces ultrastrong plasmonic coupling betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
135
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(137 citation statements)
references
References 41 publications
(17 reference statements)
2
135
0
Order By: Relevance
“…Some of them are markedly higher than those of gold nanorods (22%), gold nanoshells (13%), gold nanocages (18%) and gold nanostars (17.9%) [48,49]. In agreement with the fact that Ru2 complex had the highest TPL of the complexes studies in this work, the Ru2@AuNPs were found to have the highest temperature increase.…”
Section: Photothermal Properties Of the Ru@aunpssupporting
confidence: 76%
“…Some of them are markedly higher than those of gold nanorods (22%), gold nanoshells (13%), gold nanocages (18%) and gold nanostars (17.9%) [48,49]. In agreement with the fact that Ru2 complex had the highest TPL of the complexes studies in this work, the Ru2@AuNPs were found to have the highest temperature increase.…”
Section: Photothermal Properties Of the Ru@aunpssupporting
confidence: 76%
“…65,66 PAI has the advantage of deep tissue penetration as a result of the ultrasonic wave produced by the pulsed laser 67,68 and can be utilized to investigate tumor-targeting effects. The bare Bi 2 Se 3 NSs and Bi 2 Se 3 -CS-RGD NSs are injected intravenously (1 mg ml −1 , 0.1 ml) into tumor-bearing nude mice, and the PA images are acquired 2-18 h post injection.…”
Section: In Vivo Imaging and Biodistribution Investigationsmentioning
confidence: 99%
“…22,23 The absorbance in the NIR region 4 and photothermal conversion (PTC) efficiency are two key parameters that determine the efficacy of a PTC agent. 24 Owing to the lower PTC efficiency of the clustered Fe 3 O 4 particles, their absorbance in the NIR region is still inadequate for clinical applications in the field of cancer therapy.…”
Section: Introductionmentioning
confidence: 99%